The wavelet analysis: The case of non-performing loans in China - Elisa Di Febo; Eliana Angelini (Risks, 2022)
China has accelerated its banking sector reform in recent years, paying particular attention to non-performing loans (NPLs). The paper's scope is to analyse the relationship between NPLs and macroeconomic variables in China using quarterly data from 2008/Q1 to 2021/Q1 applying wavelet analysis, which allows the study to scan both short- and long-term causal relationships and connections. The analysis produces interesting results. The GDP does not appear to be as important and as much of a driving force in the dynamics of NPLs as in other emerging countries. On the other hand, inflation shows a highly dynamic dependence on NPLs as it varies over time; however, the most interesting data is the relationship between NPLs and economic policy uncertainty. In the short term, the variables are in phase. In the long term, an increase of EPU has a reduction effect on NPLs, indicating that it affects commercial bank loan sizes by reducing enterprise demand for and bank supply of credit resources.
Keywords: 330; non-performing loans; China; wavelet analysis; GDP; EPU; CPI